Media Literacy and its Role in Countering Hybrid Warfare (the Case of Ukraine) - Isabela de Andrade Gama; Wiktor Możgin (International Society of Philosophy and Cosmology, 2021)
The vast majority of contemporary conflicts between states are of a hybrid nature. This is due to the complexity of processes taking place in the international arena. One aspect of the hybrid nature of conflicts is the issue of information warfare. The Ukrainian-Russian conflict, which has lasted since 2014, contains all the attributes of a hybrid conflict. Understanding and a thorough analysis of the relations between these countries require the atomization of the scope of the concept of hybrid war and its individual fragments. The authors of this article focus on the issue of information warfare carried out by the Russian Federation in relation to Ukraine and the issue of media literacy in the educational sphere as a tool aimed at counteracting this type of destructive policy by the Kremlin.